2021
DOI: 10.3389/fmed.2021.744592
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: The First Reported Case of Bullous Lichen Planus-Systemic Lupus Erythematosus Overlap Syndrome

Abstract: Introduction: Lichen planus/lupus erythematosus overlap syndrome is rarely seen in the clinic and has the characteristic clinical manifestations, histopathology, and immunopathology of lichen planus (LP) and lupus erythematosus (LE). This is the first reported case of bullous lichen planus (BLP)/systemic lupus erythematosus (SLE) overlap syndrome with hair loss as the first symptom.Case Presentation: A 48-year-old female presented with alopecia for half a year, and skin lesions accompanied by itching on her fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…In a similar vein, Lucpinozo et al used 50 mg of Astressin, and Patil et al reported that Methotrexate was successfully used for HIV+ patients with OLP. However, unlike previous articles, we also used the topical effect of a corticosteroid drug used by the patient as a systemic drug (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, Lucpinozo et al used 50 mg of Astressin, and Patil et al reported that Methotrexate was successfully used for HIV+ patients with OLP. However, unlike previous articles, we also used the topical effect of a corticosteroid drug used by the patient as a systemic drug (16,17).…”
Section: Discussionmentioning
confidence: 99%